Analisis Pemilihan Enterprise Resource Planning (ERP) Menggunakan Analytical Hierarchy Process (AHP) Studi Kasus Pada PT. Laba Usaha Mandiri - Firdaus, Mohamad (Jurnal Teknologi Informasi (JUTECH), 2023)
Enterprise Resource Planning (ERP) can be used as a concept of organizational resource planning and management to generate added value for the company. PT. Laba Usaha Mandiri as an oil palm plantation startup is trying to improve its organization by trying to implement an ERP system to support daily operations. It is important that the ERP system selection process is carried out properly and correctly. And due to budget reasons, open source ERP was chosen for this problem. The selection of ERP system software for this company became the subject of a survey using quantitative methods using primary data and secondary data as samples. The results of testing and analysis using the Analytical Hierarchy Process (AHP) methodology are expected to be a guideline for the management of PT. Laba Usaha Mandiri to choose their ERP correctly